A multi-center, prospective, open-label, 8-week study of certoparin for anticoagulation during maintenance hemodialysis - the membrane study - Dorsch, Oliver Kurt; Harenberg, Job (BMC nephrology, 2012)
Background: Adequate anticoagulation is prerequisite for effective hemodialysis to prevent clotting in the extracorporeal circuit. We aimed providing first data on the efficacy and safety of the low-molecular-weight heparin certoparin in this setting. Methods: Multicenter, open-label, 8-week trial. Patients received a single dose of 3,000 IU certoparin i.v. with additional titration steps of 600 IU and/or continuous infusion if necessary. Results: 120 patients were screened, 109 enrolled (median age 71; range 26-90 years) and 106 available for efficacy analyses. The percentage of unsatisfactory dialysis results at 8 weeks due to clotting or bleeding, was 1.9% (n = 2/106; 95% confidence interval [CI] 0.23-6.65%); no major bleeding. 1.9% had moderate/severe clotting in the lines/bubble catcher and 2.8% in the dialyser at week 8. 15.7 ± 14.3% of the dialysis filters’ visual surface area was showing redness. In subgroups of patients receiving median doses of 3000 ± 0, 3000 (2400-6000) and 4200 (3000-6600) IU, plasma aXa levels at baseline, 4 and 8 weeks were 0.24 [95%CI 0.21-0.27], 0.33 [0.27-0.40] and 0.38 [0.33-0.45] aXa IU/ml at 2 h. C48h was 0.01 [0.01-0.02] aXa IU at all visits. At baseline and 4 weeks AUC0-48h was 2.66 [2.19-3.24] and 3.66 [3.00-4.45] aXa IU*h/ml. In 3.0% of dialyses (n = 83/2724) prolonged fistula compression times were documented. Eight patients (7.34%) had at least one episode of minor bleeding. 4) 85.3% of patients had any adverse event, 9.2% were serious without suspected drug relation; and in 32 patients a drug-relation was suspected. Conclusions: Certoparin appears effective and safe for anticoagulation in patients undergoing maintenance hemodialysis.